Competitive reactive adsorption desulphurization of dibenzothiophene and hydrogenation of naphthalene over Ni/ZnO. (11th December 2017) - Huang, Lichun; Ge, Hui; Yan, Lai; Wang, Guofu; Qin, Zhangfeng; Wang, Jianguo
Abstract: Ni‐based catalysts are good alternatives to noble metal ones for hydrogenation. However, few effective sulphur‐resistant supported Ni catalysts are available commercially so far. This paper presents a Ni/ZnO catalyst prepared by coprecipitation. The optimal calcination temperature is found to be 350 °C. A set of experiments were conducted with addition of naphthalene and dibenzothiophene (DBT) as a model diesel. The reactive adsorption desulphurization activity increases with increasing reaction pressure. The Ni/ZnO catalyst exhibits high activity for naphthalene hydrogenation. The presence of naphthalene caused inhibition of the hydrogenation route and the conversion of DBT decreased slightly. DBT inhibited the hydrogenation of naphthalene and the conversion of naphthalene is 98 % and remained unchanged before 20 h time on stream at 0.4 MPa.